Determinantes da probabilidade de atendimento de reclamações nos órgãos de defesa do consumidor: uma análise econométrica do cadastro nacional de reclamações fundamentadas - Pereira Junior, João Batista (2014)
The present work promoted an analysis of the National Register of founded Complaints of the year 2011 (publication happened in 2012) whose base of data possesses 153.094 observations, which represent all of the complaints formulated in this period in consumer defense organs spreaded in all areas of the national territory. Logistic Regressions were performed in order to determine a probabilistic measure that reflects the possibilities of success to consumers' demands together the entities and organizations created for discussion and processing of demands. The proposed econometric model took into account sex and consumers' age group, the subject discussed in the processes, the geographical location where happened the complaint, besides the field of activity of the claimed suppliers. With the accomplished simulations, among other results, it was verified that the largest success chances on the national scene for females aged 31-40 years are for the demands that involve products (67.3%) and that the housing sector presented the lowest probability of celebrating conciliation between the parties (39.1%).